Inspecting map compilation in earth sciences for better communication - Pál, Márton; Albert, Gáspár (Hungarian Geographical Bulletin, 2021)
The use of thematic cartography in earth sciences is a frequent task for researchers when publishing. When creating a map, researchers intend to communicate important spatial information that enhances, supplements or replaces textual content. Not only visual but substantial requirements exist for those who create maps. Cartographic visualisation has several well-established rules that must be taken into account during compilation, but not all researchers apply them correctly. The present study aims to identify the factors determining the quality of geoscientific maps and what needs to be improved during a map compilation process. To get to know the tendencies, we have investigated maps in designated journals – one Hungarian and one international per earth science branch: geography, cartography, geology, geophysics, and meteorology. A system of criteria was set up for evaluating the maps objectively; basic rules of cartography, quality of visual representation, and copyright rules were investigated. The results show that better map quality is connected to journals with strict editorial rules and higher impact factors. This assessment method is suitable for analysing any kind of spatial visual representation, and individual map-composing authors can use it for evaluating their maps before submission and publication.